Supplementing probiotics during early stages of mud crab (Scylla paramamosain) culture under various rearing systems - Ong, Moc Quy (Curtin University, 2018)
The study aimed to improve megalopa and crablets production of mud crab, Scylla paramamosain, through dietary supplementation of probiotics and locally available diets under various rearing systems. The results concluded that the probiotic-enriched live food fed until the late zoeal stage in a green water culture system increased the megalopa production. Megalopa fed live Acetes resulted in increased survival. However, the production of crablets and not megalopa, was compromised when green water culture was employed.